Current Treatment Options for Osteoarthritis - Hermann, Walter; Lambova, Sevdalina; Muller-Ladner, Ulf (Current Rheumatology Reviews, 2018)
Osteoarthritis (OA) is the most common joint disease and a leading cause for impaired function and disability with significant treatment costs and socio-economic burden. Despite recent achievements in the knowledge on disease pathogenesis, the treatment is still a challenge and contrary to the inflammatory joint diseases, no disease-modifying drugs are currently available for OA. Different response in different localizations of the disease further complicates the therapeutic choice. The standard pharmacological treatment includes agents for control of pain and inflammation (non-steroidal anti-inflammatory drugs, analgesics including opioids, intraarticular corticosteroids) and the group of the symptomatic slow acting drugs for OA such as glucosamine sulfate, chondroitin sulfate, diacerein, unsaponifiables extract of soybean and avocado administered orally and intrarticular hyaluronic acid. In addition, a number of studies investigate the efficacy of classic disease-modifying drugs used in inflammatory arthritides and antiresoptive agents as potential future therapies that could prevent structural progression of the disease. In a number of small studies, therapeutic efficacy of hydroxychloroquine (HCT) in OA has been suggested, but the results are contradictory. The first results from a multicenter, randomized, double-blind, placebo-controlled trial focused on symptomatic hand OA were recently reported (British HERO study). It has been concluded that HCQ was not superior than placebo as analgesic treatment or for reduction of the radiographic progression in hand OA. Placebo-controlled trial evaluating the efficacy of HCT in inflammatory and erosive hand OA is under way (OA TREAT study). Another field of recent research is the efficacy of TNF-alpha blockers based on the knowledge of their high efficacy in the inflammatory joint diseases and the significant role of TNF-alpha in the pathogenesis of OA. However, current evidence from the available studies does not support the use of TNF-alpha blockers in OA. The benefit of TNF-alpha blockers in specific sub-groups of patients with higher level of inflammation, objective criteria for the expected responders as well as cost-effectiveness of such treatment is a matter of further research and discussion. New biologic agents that target the nerve growth factor-β are other currently investigated drugs as a potential symptomatic therapeutic option in OA. Significant research has been also focused on revealing potential symptomatic or eventually disease-modifying efficacy of drugs that target bone metabolism due to contemporary notion for the crucial role of the subchondral bone in OA pathology and the positive association between the increased subchondral bone turnover and the progressive cartilage loss. A significant delay of joint width narrowing vs. placebo has been observed in patients with symptomatic knee OA after treatment with strontium renelate. The intraarticular administration of platelet-rich plasma is evaluated as potential future therapy and has been tried in knee and hip OA with beneficial effect. Based on the current knowledge about the OA pathogenesis and the undergoing studies, new therapies for OA are awaited both as a safe symptomatic treatment - alternative to the conventional treatment options and as a disease-modifying therapy that would revolutionize the contemporary approach to OA.
Keywords: antiresoptive agents